" اختلاف ِامت سے متعلقہ احادیث کی روشنی میں راہِ حق کی تعیین ایک تحقیقی اور تنقیدی مطالعہ The difference in Umm’ah in the light of the relevant tradistions and the configuration of the righteous path A scholarly and critical review " - ضىاء الحق; عبد الرحمن (الإيضاح, 2014)
a great deal of research work has been done upon the differences present in the Muslim Umm’ah and for its dissolution. Hence, scholars like Ashari, Baghdadi, Ibn al- Hazm and Shehristani has produced great critical and analytical studies, however the sect proclaiming on “Rah-e –Haq" (the truly guided path) needs critical review. In this article, a scholarly analysis and estimation of the "Rah-e-Haq"sect (the guided ones) is being attempted in the light of the relevant traditions.